Examining User Involvement in Continuous Software Development (A case of error reporting system). - MUTHITACHAROEN, ACHITA (MI); SAEED, KHAWAJA A. (Communications of the ACM, 2009)
The article reports on user involvement in continuous computer software development. Computer software companies, in order to maintain adequate levels of customer satisfaction, spend an estimated 50-75% of total software development costs on testing the software, eliminating errors in the software, and verification activities. However, it is difficult to eliminate all errors in computer software and so companies have involved computer users in the process of error reporting with an error reporting system where the computer user informs the company directly or through a third party vendor.